Parameter combination norfloxacin and tylosin on poultry: A review - Wibisono, Cahyo; Pamudya, Kanya Gabriella Sasri; Wijayanti , Agustina Dwi; Widiasih , Dyah Ayu; Tjahajati, Ida; Indarjulianto , Soedarmanto (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2025)
The use of antibiotics is currently one of the most widely used drugs. Various types of antibiotics that have been distributed, both broad spectrum and narrow spectrum, have caused several side effects. One of the side effects currently occurring is antibiotic residue and antimicrobial resistance. Antibiotic residues occur due to remaining drug metabolism residues not being excreted in full. Antimicrobial resistance occurs due to the use of antibiotics at inappropriate doses. If this incident occurs continuously it will have significant global effects which will directly affect human and animal health in the future. Pharmacokinetic studies really need to be carried out to determine the profile of a drug in the body. Pharmacokinetics describes the time course of drug levels in body fluids as a result of absorption, distribution and elimination of the drug after administration to avoid antimicrobial resistance and provides information regarding the pharmacokinetic parameters of the use of the combination of norfloxacin and tyrosin in birds and as well as information regarding the pharmacokinetic description of the combination of norfloxacin and tyrosin in poultry.